Glycan-Glycan Interaction Determines Shigella Tropism toward Human T Lymphocytes - Ilia Belotserkovsky (American Society for Microbiology, 2018)
ABSTRACT Direct interactions between bacterial and host glycans have been recently reported to be involved in the binding of pathogenic bacteria to host cells. In the case of Shigella, the Gram-negative enteroinvasive bacterium responsible for acute rectocolitis, such interactions contribute to bacterial adherence to epithelial cells. However, the role of glycans in the tropism of Shigella for immune cells whose glycosylation pattern varies depending on their activation state is unknown. We previously reported that Shigella targets activated, but not nonactivated, human CD4+ T lymphocytes. Here, we show that nonactivated CD4+ T lymphocytes can be turned into Shigella-targetable cells upon loading of their plasma membrane with sialylated glycosphingolipids (also termed gangliosides). The Shigella targeting profile of ganglioside-loaded nonactivated T cells is similar to that of activated T cells, with a predominance of injection of effectors from the type III secretion system (T3SS) not resulting in cell invasion. We demonstrate that gangliosides interact with the O-antigen polysaccharide moiety of lipopolysaccharide (LPS), the major bacterial surface antigen, thus promoting Shigella binding to CD4+ T cells. This binding step is critical for the subsequent injection of T3SS effectors, a step which we univocally demonstrate to be dependent on actin polymerization. Altogether, these findings highlight the critical role of glycan-glycan interactions in Shigella pathogenesis. IMPORTANCE Glycosylation of host cell surface varies with species and location in the body, thus contributing to species specificity and tropism of microorganisms. Cross talk by Shigella, the Gram-negative enteroinvasive bacterium responsible for bacillary dysentery, with its exclusively human host has been extensively studied. However, the molecular determinants of the step of binding to host cells are poorly defined. Taking advantage of the observation that human-activated CD4+ T lymphocytes, but not nonactivated cells, are targets of Shigella, we succeeded in rendering the refractory cells susceptible to targeting upon loading of their plasma membrane with sialylated glycosphingolipids (gangliosides) that are abundantly present on activated cells. We show that interactions between the sugar polar part of gangliosides and the polysaccharide moiety of Shigella lipopolysaccharide (LPS) promote bacterial binding, which results in the injection of effectors via the type III secretion system. Whereas LPS interaction with gangliosides was proposed long ago and recently extended to a large variety of glycans, our findings reveal that such glycan-glycan interactions are critical for Shigella pathogenesis by driving selective interactions with host cells, including immune cells.